Estimating Working Life Expectancy: A Comparison of Multistate Models - Holendro Singh Chungkham; Robin S. Högnäs; Jenny Head; Paola Zaninotto; Hugo Westerlund (SAGE Open, 2023)
Increases in retirement ages make it particularly pressing to better understand how long people will work. Working life expectancy (WLE) is a useful measure for this and the current paper assesses the tools, that is, software packages, available to assess it. We do this using data from the English Longitudinal Survey on Ageing (ELSA, 2003–2018) and multistate models to estimate WLE stratified by sex and socioeconomic status. Men’s versus women’s WLEs were slightly higher at all ages. Estimates were similar in ELECT and SPACE by both sex and socioeconomic status. WLEs were comparatively higher from IMaCh, ranging from approximately 0.28 to 1.49 years. Life expectancy estimates from IMaCh were also higher compared to SPACE and ELECT. Using multistate models to estimate WLE provides a useful indication of the actual expected length of working life. More research is needed to better understand why estimates from IMaCh differed from ELECT and SPACE.